Aperfeiçoamento da hidrodestilação, determinação da composição dos óleos Lippia lasiocalycina cham. E Lippia insignis moldenke e efeito das nanoemulsões em mosca do mediterrâneo - Santana, Taris Maria Macedo de (2019)
The organic food market is growing, as consumers are increasingly opting for more natural products. In addition, there is an rise in crop pest resistance, which has led to the increasing use of chemical pesticides. In Brazil, Mediterranean fruit fly (Ceratitis capitata) is one of the obstacles that hinders the growth of the fruit trade. In this scenario, biopesticides have been gaining ground, and essential oils (EO) occupy a prominent position. Lippia insignis and Lippia lasiocalycina are native semi-arid species that produce essential oils that have proven to be effective against Ceratitis capitata. This study aimed to improve the hydrodistillation of OE of L. insignis and L. lasiocalycina aiming at higher yield and better quality to be used as insecticides. Due to the great volatility of the OEs, the search for formulations that can improve its stability and effectiveness has been constant. Thus, this study also aimed to develop nanoemulsions of the OEs of these species using polysorbate and ultrasound as a method to produce stable and efficient nanoemulsions against adults and C. capitata larvae. The results showed that the use of less water and less time increases the EO yield of the species and the chemical composition may change depending on the factors studied (solvent ratio: biomass and time). The nanoemulsions of L. insignis and L. Lasiocalycina have nanometric characteristics and have been shown to be stable and efficient as insecticides.